ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LAMA WAKTU MEMPEROLEH PEKERJAAN DI INDONESIA - Damayanti, Reyna (Journal of Development Economic and Social Studies, 2023)
The number of Indonesian workers has increased every year and the lack of job opportunities has become a major obstacle to the development of the employment sector in Indonesia. Opportunities to get a job are decreasing, causing unemployment. Using the robust regression analysis method, this research tries to look at the factors that influence the length of time it takes to get a job in Indonesia. The data used comes from the 2019 National Labor Force Survey (SAKERNAS). The results show that the level of education, effort to find work, and the UMP level have a significant positive effect on the length of time to find a job in Indonesia. Meanwhile, age and job training have a significant negative effect on the length of time to get a job in Indonesia. Therefore, the government and related parties can consider these factors in making decisions, especially to overcome and deal with employment issues regarding unemployment regarding the length of time to get a job or the duration of unemployment.